IDENTIFIKASI PRODUK ATRAKSI DAN SEGMENTASI PASAR PARIWISATA HALAL (STUDI DI CLUSTER KUTA, KABUPATEN LOMBOK TENGAH, PROVINSI NUSA TENGGARA BARAT) - Ulfatun Hasanah (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
According to the 2016 Global Muslim Travel Index (GMTI), MasterCard & CrescentRating Indonesia ranks 4th as a destination visited by world Muslim tourists in 2015. The evaluation criteria are Halal food, prayer facilities, friendly water-use washrooms, ramadhan services, no non-halal activities, recretional facilities and services with privacy, segmentation of Muslims. Halal tourism is a new concept to develop tourism in Muslim countries in the world. The Province of West Nusa Tenggara (NTB) in 2015 received an international award at the 2015 World Halal Travel Awards held in the United Arab Emirates on October 20, 2015. There were 2 (two) awards received by the West Nusa Tenggara Province, The World's Best Halal Tourism Destination and The World's Best Halal Honeymoon Destination. The strength possessed to develop halal tourism is the strong religious values ​​embraced by the community, the huge share of the halal tourism market has not been utilized properly by other regions so NTB needs to develop it, and the culture that develops in the community attracts foreign tourists. So that to develop halal tourism it is necessary to identify tourist attraction products and halal tourism market segmentation. Halal tourist attractions are divided into 3 namely natural, cultural, and artificial. The criteria for halal tourist attractions are: a) Art and cultural performances and attractions that do not conflict with the general criteria of sharia tourism appropriate (cleanliness and availability of water for purification) in tourism objects, e) Halal food and drinks are available. Segmentation of the halal tourism market consists of the age of tourists, employment, education, entrance, destination, pattern of travel, areas visited, tourist activities, sources of information. The type of research used in this study is descriptive research using a qualitative approach that understands deeply about the object under study.